Challenging Myelopathy Cases - Mustafa, Rafid; Zalewski, Nicholas L.; Flanagan, Eoin P.; Kumar, Neeraj (Seminars in Neurology, 2022)
Misdiagnosis of myelopathies is common and can lead to irreversible disability when diagnosis- and disease-specific treatments are delayed. Therefore, quickly determining the etiology of myelopathy is crucial. Clinical evaluation and MRI spine are paramount in establishing the correct diagnosis and subsequently an appropriate treatment plan. Herein, we review an approach to myelopathy diagnosis focused on the time course of neurologic symptom progression and neuroimaging pearls, and apply them to a variety of inflammatory, structural, and vascular myelopathy cases.
Keywords: myelitis; spondylosis; spinal cord infarction; dural arteriovenous fistula